The given expression : y-1=2/3(x-3)
Simplify the equation :
![\begin{gathered} y-1=(2)/(3)(x-3) \\ y=(2)/(3)x-(2)/(3)(3)+1 \\ y=(2)/(3)x-2+1 \\ y=(2)/(3)x-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jfg8xqbkbbccori3qbzkfkoc50xww7j11v.png)
for the graph we need atleast two coordinates
Let at x=0 then
y=2/3(0)-1
y=-1
Cooridnate = (0,-1)
Now, let x=9 then
y=2/3(9)-1
y=2(3)-1
y=5
Coordinate =(9,5)
Plot these point (0,-1) & (9,5)on the graph and join them by staright line
The graph will be ;